What Drives Islamic Entrepreneurial Intention? Evidence from Muslim Youth in Indonesia - Maulana, Denis Muafa Dhiaul Adha; Manggala Putri, Syah Amelia; Aarón A. Vargas-Zeledón (Journal of Islamic Economic and Business Research, 2026)
The high unemployment rate in Indonesia underscores the importance of fostering entrepreneurship, particularly Islamic-based entrepreneurship. This study aims to analyze the influence of religiosity, self-efficacy, income expectations, and social support on Islamic Entrepreneurial Intention (IEI) among final-year students and alumni from universities in Yogyakarta. The study involved 307 respondents and employed a quantitative approach. Data were collected via an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings indicated that all four independent variables, religiosity, self-efficacy, income expectation, and social support, positively and significantly affect IEI. These results support the relevance of the Theory of Planned Behavior (TPB) in explaining Islamic entrepreneurial intention. The practical implication of this study is to emphasize the importance of synergy between strengthening religious values, self-confidence, social support, and income expectations in fostering Islamic entrepreneurial spirit among the younger generation.